2011
DOI: 10.5539/ijbm.v6n8p34
|View full text |Cite
|
Sign up to set email alerts
|

The Mediating Effects of Customer and Competitor Orientations on New Product Success

Abstract: Market orientation, innovation, and new product success are receiving increasing attention from practitioners and scholars. Although producing new products is critical to the profitability of a firm and its long-term survival, it is a costly and risky business because of low success rates. The research on which this paper is based investigated key determinants of new product success from the perspective of team members responsible for developing new products. Findings from 217 respondents support the hypothese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 96 publications
0
12
0
1
Order By: Relevance
“…Hopkins (1980) studied 148 industrial product manufacturing fi rms and concluded that new product failure can be reduced by educating customers, avoiding the over-engineering of new products and performing market research. Wong et al (2011) found that the degree to which an organisation exhibits a customer orientation mediated the impact of that organisation's marketing-R&D collaboration on new product success. Major problems that lead to product failure include an organisation's lack of preparation to market products, an organisation's inability to support fast market growth, and the commercialisation of new products that fall short of customer expectations.…”
Section: New Product Market Successmentioning
confidence: 99%
“…Hopkins (1980) studied 148 industrial product manufacturing fi rms and concluded that new product failure can be reduced by educating customers, avoiding the over-engineering of new products and performing market research. Wong et al (2011) found that the degree to which an organisation exhibits a customer orientation mediated the impact of that organisation's marketing-R&D collaboration on new product success. Major problems that lead to product failure include an organisation's lack of preparation to market products, an organisation's inability to support fast market growth, and the commercialisation of new products that fall short of customer expectations.…”
Section: New Product Market Successmentioning
confidence: 99%
“…S. Wong and T. Canon (2011) investigated the mediating effects of customer and competitor orientations on new product success. This research found that R&D-marketing cooperation is a key factor for NPS, as it encourages the sharing of ideas and making of joint decisions so that tasks can be accomplished in the most effective way.…”
Section: Marketing Strategy Formulation For Innovative New Product Dementioning
confidence: 99%
“…Operational effectiveness (Delarue, Van Hootegem, Procter, & Burridge, 2008;Sparrow & Cooper, 2014) feelings (Van Dyne & Pierce, 2004;Knowledge.wharton, 2007), customer orientation (Asikhia, 2010;Jeong, Kim, & Yoon, 2014) are used. In addition, other constructs such ascompetitor orientation (Wong & Tong, 2011;Kumar, Subramanian, &. Strandholm, 2011) inter-functional orientation (Chin, Lo, & Ramayah, 2013;Hussain, Shah, & Akhtar, 2016) and social orientation (Ramayah, Samat, & Lo, 2011) are also used.Those studies found the positive relationship of operational excellence constructs and organisational performance.However, the previous studies failed to highlight the specific relationship of stakeholders.…”
Section: Operational Excellence and Organisational Performancementioning
confidence: 99%